Application of the Concept Planning, Organizing, Actuating, Controlling in Improving the Quality of Education at Madrasah Ibtidaiyah Wathoniyah Cirebon - Agustian Widia Yusuf, Ilham; Kohar, Andri; Sartrika, Ika (Journal of Leadership, Management and Policy in Education, 2024)
This study investigates the application of management functions in enhancing the quality of education at Madrasah Ibtidaiyah Wathoniyah Putra Buntet in Kabupaten Cirebon. Despite the potential for good management to improve educational quality, the current management practices at this school are ineffective and inefficient, leading to poorly implemented programs and plans. The research aims to: 1) explore the application of education management functions; 2) understand the management practices at Madrasah Ibtidaiyah Wathoniyah Putra Buntet; 3) identify factors that hinder and support quality improvement in education. The research focuses on the management functions of planning, organizing, implementing, and controlling. Utilizing a qualitative approach, the study seeks to understand the experiences of the research subjects through observation, documentation, and interviews. Data analysis involves reduction, presentation, and conclusion drawing. Findings indicate that while the management functions are recognized, their execution is insufficient, resulting in ineffective programs. Inhibiting factors include inadequate infrastructure, insufficient funding, and low-quality educators. Supporting factors are strong leadership, good coordination and cooperation, and teachers' classroom management skills.